Outcomes for Angioplasty and Bypass Lower Limb Revascularisation Procedures for Limb Salvage in England: Findings From the Getting It Right First Time Programme. (November 2020) - Gray, William K.; Day, Jamie; Horrocks, Michael
Abstract : Objective: The aim of this study was to investigate outcomes for lower limb revascularisation for limb salvage within the National Health Service (NHS) in England. Methods: This was a retrospective observational study of administrative data. Data were extracted from the Hospital Episodes Statistics database for England. Data were included for a seven year period (1 April 2011–31 March 2018 inclusive) for all patients aged ≥ 18 years receiving surgery for peripheral arterial occlusive disease. Data were extracted for patient age, sex and frailty level, the NHS trusts undertaking the procedure, the technique used (angioplasty, bypass, endarterectomy, or hybrid), the mode of admission (elective or emergency), the surgical speciality, the financial year of admission, length of hospital stay during the procedure, subsequent emergency re-admission, revascularisation procedures within 30 days and subsequent amputation and mortality within one year and within five years. The primary outcome was one year amputation free survival. For analysis, data were separated into diabetic and non-diabetic patients. Multilevel modelling was used to adjust for hierarchy and observed confounding when investigating outcomes. Results: Data were available for 98 109 procedures across 124 hospital trusts. For non-diabetic patients (odds ratio 1.142, 95% confidence interval 1.068–1.222), one year amputation free survival was higher for angioplasty than for bypass. For diabetic patients, there was no difference in the primary outcome. One year amputation rates, 30 day emergency re-admission rates, and length of stay were all lower for angioplasty, and 30 day revascularisation rates were lower for bypass for both diabetic and non-diabetic patients. Conclusion: Outcomes were generally better for angioplasty than for bypass surgery for lower limb revascularisation for both diabetic and non-diabetic patients. The findings should be interpreted with caution given the likely different clinical presentations of those selected for each procedure. Future clinical trials may provide more definitive data.